Antisepsys and profilatic antimicrobial therapy in prevention of surgical site infection of horses - Canola, P. A. [UNESP]; Faria, A. P. P. A. [UNESP]; Paula, V. B. [UNESP]; Avila, F. A. [UNESP]; Cardozo, M. [UNESP]; Rivera, G. G. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
The efficacy of an antisepsis protocol comprising chlorhexidine gluconate and ethyl alcohol in combination with prophylactic antimicrobial therapy in controlling surgical site infection in horses was studied. To that purpose, seven mixed breed horses received potassium penicillin and gentamicin at least 30 minutes prior to surgery. The surgical site was scrubbed with chlorhexidine gluconate and rinsed with ethyl alcohol. Samples were collected at four time points: (A) - before and (B) - immediately following shaving of the hair coat, (C) at the end of antisepsis procedures, and (D) - at the end of the surgical procedure. Duration of surgery was recorded. Samples were cultured in three different culture mediums: Mitis Salivarus (Streptococcus sp.), Staphylococcus 110 (Staphylococcus sp.), and Mac Conkey ( Enterobacteria). A high level of bacterial growth was observed in all culture mediums at (A) and (B), with no bacterial growth in (C). Staphylococcus sp. growth was observed in (D) in a single patient whose surgical procedure lasted for 120 minutes. Shaving of the hair coat reduced microbial flora on the surface of the skin. Antisepsis in combination with prophylactic antimicrobial therapy was effective in controlling surgical site infection in elective procedures with an average duration of 90 minutes.
Keywords: chlorhexidine gluconate; culture media; potassium penicillin; Staphylococcus sp; SSIs